Abu Shakur al-Salimi's Views on Caliphate - ÜMİT, MEHMET (ATATURK UNIV, FAC THEOLOGY, 2019)
The Caliphate/Imamate was one of the most important issues among the Muslims following the death of the Prophet. This issue, especially with Shia, has been moved from the political area to the theological area. As a matter of fact, the Sunni theologians probably with the influence of Shiite scholars, included the Imama/Khilafa issue in their kalami issued and gave place to it in their works. One of them is the theologian Abu Shakur al-Salimi (d. after 460/1068) from Samarkand region. In the Hanafi biographical books, there is not much information about the life of Abu Shakur. On the basis of some of the information given in his own work al-Tamhid fi bayan at-taw id, it is estimated that Abu Shakur was born at first half of 5th century of the Hegirah (11th century). In this work, Abu Shakur mainly dealt with the following issues: the mind/reason, the existence of Allah, the oneness of Allah, the names and attributes of Allah, miracles, revelation, the Miraculousness of Qur'an, literal kalam-spiritual kalam, the conditions of faith, caliphate and imamate, Ahl as-Sunnah, Ahl al-Bid 'ah. As the title implies, in this paper, we will try to put forward the views of Abu Shakur al-Salimi on Khilafa/Imamate issue based on his work al-Tamhid fi bayan at-taw id. In this context, the views of the author about the meritorious virtues of the Companions of the Prophet will be pointed out. In addition, the criticism of Abu Shakur al-Salimi regarding the Shia's understanding of imamate will be examined. These issues, which the author deals with, are probably among the topics discussed in the region during his period.
Keywords: Caliphate; Imamate; Shia; Hanafi; Maturidi; Abu Shakur al-Salimi